Consultative Workshop on Integrating Climate Risk Management in Agricultural University Curricula - Belay, Berhanu; Dinku, Tufa; Demissie, Teferi Dejene; Grossi, Amanda; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate impacts pose enormous challenges to agricultural productivity and exert pressure on its profitability by increasing the riskiness of farmers' decisions. Climate risk is a significant barrier to adopting improved farming practices and production inputs, especially for relatively poor smallholder farmers in risk-prone environments. Climate risk also leads to uncertainty in the decision-making of other actors in the food system, including agricultural value chains, rural financial services, government planning, and humanitarian and government organizations responsible for disaster management. Thus, advances in climate science and improved availability of locally relevant climate data and information products can expand potential options for understanding, anticipating, and managing climate-related risks in the agricultural sector. Although the impact of climate-related risks has many facets in agriculture and the food system, the understanding and use of practical tools to manage climate risks are not well integrated into university-level curricula. This has led to Ethiopian public universities' engagement to advance skill-based climate curriculum through continuous consultation. The first proposed curriculum is a three-week customized training for Staff, M.Sc. students, and Ph.D. students. By developing staff and students' practical skills, this curriculum plans to integrate CRM courses in university curricula in various forms.